Perencanaan Infrastruktur Kawasan Minapolitan - Yashinta Kumala Dewi Sutopo; Muhammad Fathien Azmy; Nurul Aisyah Salman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2016)
The purpose of this study is to present the types of infrastructure that must be had by Minapolitan in achieving its objectives and to analyze the current and future demand of road infrastructure and rural water supply. The selected case study is the Minapolitan Pangkajene Kepulauan Region (Pangkep). This research was conducted in 3 months (starting from June to August 2015) based on literature studies and field surveys. The study concludes that, in general, marine and fisheries support infrastructure plans for Minapolitan should focus on providing and improving rural roads, clean water supply, fishing ports, fish processing units, hatcheries, and fish markets. The plan must also cover the provision and improvement of basic infrastructure for local communities such as fishing housing, education, health facilities, waste disposal systems, energy and telecommunications. A survey and analysis of road and water supply in the case study area concluded that although overall services were available, program improvements were still needed, especially those relating to the quality of rural roads and the capacity of the water supply system.